Desaparecimento de misturas minerais de livre consumo para bovinos a pasto e sua associação com a precipitação pluviométrica - ZEY WELINGTON GOMES DE SOUZA (2023)
The aim of the present study was to evaluate the association between rainfall and the disappearance of mineral mixtures fed to cattle on pasture. Supplement consumption and rainfall information were obtained from five experiments carried out between 2016 and 2022, all carried out in the spring/summer/autumn period, in Campo Grande, MS, Brazil. The experiments lasted from 84 to 126 days and had 12 to 18 paddocks formed by Brachiaria spp, under grazing by cattle, receiving mineral supplementation. Supplement disappearance (SD, difference between offered amount and remainings) and rainfall (RF) were measured over periods of 14 to 21 days. The periods (n=565) were classified as very dry, dry, normal, rainy and very rainy, using the quantile method. The number of rainy days (RD) and average rainfall per RD (RFRD) were also determined by period and the average live weight in the periods was determined (BW). Linear regression analyzes were performed to assess the association between BW, RF, RD and RFRD. The average RF in the periods studied was 68.5 mm, ranging from 0.00 mm to 160.3 mm. Each period had up to six RD, with up to 129.5 mm precipitated per RD. The average BW was 270 kg, ranging from 208 to 335 kg and the mean SD was 82.2 g animal day-1, ranging from 0.52 to 176.7 g animal day-1. Differences in RF and RFRD are consistent between precipitation classes. However, the very rainy class had fewer rainy days than the rainy class. In the regression analysis, the model with the highest coefficient of determination was the one containing the linear and quadratic terms for the RD variable. The inclusion of linear and quadratic terms of all variables in a multiple regression was able to represent more than half of the variation in supplement disappearance (R2=0.5823). It is not clear whether there is a relationship between the classes of RF and SD, however, variables that characterize the precipitation pattern are more relevant than BW to explain the existing variations in the disappearance of supplement, and the number of days rainfall in the period seems to be the most important variable. Keywords: disappearance of supplements, precipitation pattern, quantiles